Prognostic Nutritional Index Predicts Early Mortality in Diffuse Large B-cell Lymphoma - Erman OZTURK; Tayfun ELIBOL; Emrah KILICASLAN; Beyza KABAYUKA; Işıl ERDOGAN OZUNAL (Medeniyet Medical Journal)
Objective: The international prognostic index (IPI) and the revised IPI (R-IPI) are used to determine the prognosis in diffuse large B-cell lymphoma (DLBCL). However, these scoring systems are insufficient to identify very high-risk patients. Recently, the prognostic nutritional index (PNI) -calculated with lymphocyte count and albumin- has been used to determine the prognosis in DLBCL. This study aimed to evaluate the effect of PNI score on prognosis and survival in patients with high-risk DLBCL. Methods: Patients diagnosed with DLBCL and treated with rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone were included. Pre-treatment IPI, R-IPI, and PNI scores and progression-free survival (PFS) and overall survival (OS) times were calculated. The cut-off value for PNI according to OS was determined by using the X-Tile program. Results: One hundred and ten patients were included, the median age was 63 years and the median follow-up period was 25 months. According to R-IPI, the me-dian OS could not be reached for the very good risk group, and the median OS values were 83 and 17 months in the good and poor-risk groups, respectively (p=0.001). The cohort was divided into three groups according to the cut-off value for the PNI: patients with PNI <33 were classified as high-risk, 33-42 intermediate-risk, and ≥42 as low-risk. According to PNI, the median durations of PFS and OS were 2 months and 3 months in the high-risk group, 9 months and 19 months in the inter-mediate-risk group respectively, and in the low-risk group the median duration for PFS and OS could not be reached (p=0.001). Conclusions: The R-IPI is widely used to estimate the prognosis in DLBCL. But in our cohort, in the poor-risk patient group, the OS was 17 months according to R-IPI, while this period was 3 months according to PNI. This finding demonstrated that PNI might predict early mortality in DLBCL.